Late-Adult and Elder Women Are More Susceptible To Vitamin D Insufficiency In Eastern Nepal: A Hospital-Based Retrospective Study - Mallick, Ram L. (International Journal of Pharmaceutical & Biological Archive, 2016)
Vitamin D is present in natural foods such as milk, fish, fish-liver oils, egg yolks and dairy products. Human body, in addition, produces vitamin D in response to the exposure to sunlight. Vitamin D deficiency, however, is common in children and adults. Rickets appears if an individual suffers from vitamin D deficiency. The inadequacy of vitamin D, further, retards physical growth with a risk in fracture of hip bone as individual’s age advances. Clinicians, therefore, consider vitamin D deficiency as serious health-problem and estimate its plasma concentration to determine the status as under-deficiency or over-nutrition. The estimation is crucial as deficiency of vitamin D is worldwide, being prevalent in stages ranging from degree of newborn to infancy, childhood and adult. However, the status of vitamin D was unknown among people in eastern Nepal. We, therefore, determined circulating levels of vitamin D in local population. The vitamin D insufficiency was prevalent in approximately 57 % people. By contrast, the inadequacy prevailed in 41 % individuals who were 41-60 years-old and women in same age-group had predominated the case. The state of vitamin D insufficiency was, therefore, a serious health-problem in locality.